Letters to Valaam of emigrant archpriest Simeon Solodovnikov (1930–1933) - Tatyana Shevchenko (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The publication presents letters from Paris of the period 1930-1939 by two emigrant priests - Archpriest Simeon (Solodovnikov) and then hegumen Stefan (Svetozarov). Both pastors have subordinated to Metropolitan Eulogius (Georgievsky), but after his transition to the Constantinople Patriarch subordination, they departed from him. Archpriest Simeon was subordinated to the Synod of Russian Bishops Abroad, and Hegumen Stefan remained loyal to the Moscow Patriarchate. Both wrote to the Valaam Monastery, which remained on the territory of independent Finland after the revolution and, together with the Finnish Orthodox Church, had been subordinated to the Patriarch of Constantinople since 1923. The monastery never broke the connection with the motherland, prayed for the suffering Russian Church, the Abbot corresponded with Metropolitan Sergiy (Stragorodsky) while there was an opportunity. But the monastery also tried to maintain relations with compatriots in exile. The letters confirm this. The authors shared their thoughts on the positions taken by representatives of different jurisdictions into which the Russian Orthodox community abroad split, explained their choice of jurisdiction, and talked about the difficulties of emigrant life. The letters are published for the first time and help to recreate the images of our compatriots who lost their homeland after the revolution, and to trace their further fate. In addition, the publication recreates the atmosphere of jurisdictional disputes in the Russian abroad and clarifies the motives of their participants.